Can Russia compete? - Desai ,Raj M. 1966-; Goldberg ,Itzhak 1947- (Brookings Institution Press, 2008)
"Looks at Russian governments? push toward a knowledge-based economy, particularly in the manufacturing sector. Quantifies and benchmarks sector?s relative strengths, identifying opportunities to increase Russian productivity and competitiveness. Examines underlying firm-level determinants of knowledge absorption, competitiveness, and productivity, with an eye to improving workers? skill levels and the investment climate"--Provided by publisher.